Pengaruh Kebijakan Infrastruktur Terhadap Pembangunan Ekonomi di Negara Berkembang - Anisah Nasution; Mutia Fajri Siregari; Andri Widiani; Nurhayati Harahap (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Economic growth is an indicator in measuring the success of an economy in a country. Economic growth is generally defined as an increase in the general output of goods and services produced by a country in a particular year compared to the previous year. The data collection technique used in this research is documentation techniques or methods or literature study. Data collection through documents in written or electronic form from relevant institutions or agencies regarding the variables and data that will be used in this research. The data used is road infrastructure development for five years. Based on the results of statistical analysis, the conclusion that can be drawn is that the regression model linking NATIONAL INFRASTRUCTURE DEVELOPMENT with NATIONAL ECONOMIC GROWTH DATA does not have a significant influence on the response variable. The ANOVA results show that the overall model significantly explains the variation in NATIONAL ECONOMIC GROWTH DATA at the significance level usually used (0.05). The regression coefficients for NATIONAL INFRASTRUCTURE DEVELOPMENT and the constant are also statistically significant, with p values ​​(Sig.) exceeding generally accepted thresholds.